Potential Absorption and Economic Carbon Valuation of Teak (Tectona grandis) at Hasanuddin University City Forest for Supporting Emission Reduction in Makassar City - Amru, Khaerul; Damanik, Mario; Ura', Resti; Nadjib, Nardy Noerman; Rahmila, Yulizar Ihrami (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The diversity of plants/vegetation in the UNHAS City Forest certainly has a positive impact on the environment. One type of plant species in the UNHAS urban forest is Teak (Tectona grandis L.f.). The community views Teak as a plant that only has economic potential because of the quality of its wood, but it is also necessary to know that this plant is suspected to have potential as an environmental service provider. So it is necessary to know more about the ability of teak plants to absorb carbon dioxide. Through this research, estimating carbon stored in Teak stands (Tectona grandis L.f.) was carried out by taking a case study in the City Forest at the Hasanuddin University Campus. The method of collecting emission data was collected from the Bapenas manuscript website, which was used to collect data on the potential of biomass in this study using non-destructive methods. The data collected includes the diameter, height, and specific gravity of teak trees. The diameter of the teak plant is obtained by surveying each individual teak plant. The emissions produced by Makassar City in 2022 are 6,944,242.74 tons of CO2eq. Teak trees located in the urban forest of Hasanuddin University then succeeded in reducing 455.93 - 482.48 tons of CO2eq according to carbon absorption calculations. The economic valuation of carbon reserves located in teak stands in the urban forest of Hasanuddin University ranges from USD 206.76 / Rp. 2,998,020 tons / ha to USD 218.8 / Rp. 3,172,600 tons / ha